Growth of Continental Shelves at Salt Margins - Brun, Jean-Pierre; Fort, Xavier (Frontiers in Earth Science, 2018)
Whereas salt margins are rather common, the growth of continental shelves on top of salt margins is a topic that has seldom been considered. In such settings, the sediments coming from the nearby continental areas are deposited on a viscous substratum and therefore a continental shelf can form and stabilize only if the salt layer underlying sediments does not flow or stops flowing. The present study that combines evidence from the northern Gulf of Mexico and laboratory modeling concerns more particularly those salt tectonic settings where the direction of sediment supply is oblique to the direction of salt flow because this allows to decipher between the relative effects of sedimentation and salt flow. It is shown, in both nature and experiment, that: i) shelf growth is controlled by an association of normal faults and transfer zones, ii) shelf breaks, controlled by normal faults, and transfer zones trend perpendicular and parallel to salt flow, respectively, iii) the rate of shelf break migration is faster in areas of higher sedimentation rates, iv) even at late stages of shelf growth, when the role of salt flow tends to decrease, transfer zones still remain controlled by the direction of salt flow and v) transfer zones that participated to the shaping of a continental shelf provide a precious tool to map the direction of salt flow and its variations in space and time. The interaction between salt flow and sediment supply controls the trend of the shelf envelope during shelf growth. Because the rate of salt flow decreases with time, a constant or increasing rate of sediment supply results in a rotation of the shelf envelope trend from perpendicular to salt flow direction at early stages toward perpendicular to sediment supply direction at the late stages.